Vaginal bacteria and cervical cancer: a bibliometric analysis of trends and themes - Liu, Xiaoxia; Zhao, Yinghui; Meng, Xianhua; Gao, Zheng; Wang, Xiaohong; Yang, Fengyong (Frontiers in Microbiology, 2025)
BackgroundCervical cancer remains a significant global health challenge, with increasing evidence suggesting the crucial role of vaginal bacteria in its development and progression. This study aims to analyze the global research landscape and trends in vaginal bacteria and cervical cancer research through bibliometric analysis.MethodsLiterature data were retrieved from the Web of Science Core Collection (WOSCC) database. Bibliometric analysis was performed using VOSviewer, CiteSpace, and R-bibliometrix to evaluate publication patterns, research collaboration networks, and emerging trends.ResultsA total of 372 publications were identified, showing an annual growth rate of 8.41%. China and USA emerged as leading contributors, with the Imperial College London and University of Arizona being the most productive institutions. Herbst-Kralovetz MM and Laniewski P were identified as the most influential authors, while BMC Infectious Diseases and Frontiers in Cellular and Infection Microbiology were the primary publication venues. Keyword co-occurrence analysis identified “bacterial vaginosis,” “women,” and “inflammation” as the most frequent terms, while burst detection revealed emerging research trends in “lactobacillus,” “intraepithelial neoplasia,” and “16 s rRNA gene sequencing.”ConclusionThis bibliometric analysis provides comprehensive insights into the evolution and current status of vaginal bacteria research in cervical cancer, highlighting key research themes and collaborative patterns. These findings offer valuable guidance for future research directions and potential clinical applications in cervical cancer prevention and treatment strategies.